Peningkatan Kemampuan Dosen Menggunakan Management Reference (Mendeley) dalam Membuat Karya Tulis Ilmiah - Hidayat, Rahmat; Rini Setiawati; Agus Sujarwo; Machfud Fauzi; Musa (Swadaya: Jurnal Pengabdian Masyarakat, 2023)
Implementing the Tri Dharma of Higher Education is an essential obligation for every lecturer within a higher education institution, whether at the university, institute, or college level. It involves a diverse range of tasks and characteristics aligned with licensing regulations governing scientific work management. Utilizing reference manager software, such as Mendeley and Zotero, serves as a crucial tool in maximizing support for drafting scientific articles. The primary aim is to empower lecturers and peers to effectively employ these reference manager applications in their scientific writing endeavors. This process unfolds in three sequential stages, culminating in evaluating the articles produced subsequent to the training sessions. The outcomes reveal an enhanced grasp and utilization of desktop applications like Mendeley among participants. While some individuals initially struggled with manual methods, post-training, they demonstrated a clearer understanding of Mendeley's functionality and application in crafting scientific papers. Participants not only comprehend the significance of Mendeley but also exhibit proficiency in operating the Mendeley desktop on their work devices, harnessing its conveniences for their scientific research.